PENGARUH INDONESIA-EUROPEAN UNION COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IEU CEPA) DALAM PENINGKATAN EKSPOR TEMBAKAU INDONESIA KE SPANYOL - Monica Lia Dinata; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research aims to explain about the Indonesia’s efforts to improve its economy by signing Indonesia-European Union Comprehensive Economic Partnership Agreement (IEU CEPA). Cooperation through internasional agreement can result in positive and negative effects. This research decribes how this agreement has positive impact on Indonesian tobacco export to Spain. The research uses  descriptive analysis as the method and Secondary data collections through document analysis from books, journals, newspapers, official reports from Indonesian Statistic Bureau, and websites was utilized to describe the phenomenon. Futhermore author uses the interdependence libralism perspective with nation-state level analysis and theory of international cooperation by K.J. Holsti and Free Trade Agreement model helped to analyzed the data. The result showed that the agreement has positive impacts on Indonesian for foreign exchange, increasing of tobacco export to Spain, and better earning. The agreement helped Indonesia for tariff reduction through Generalized Scheme Preference (GSP), and lower tax. Key Words: Export, Tobacco, Indonesia-European Union Comprehensive Economic Partnership Agreement (IEU CEPA), Bilateral relation, Positive and Negative Effec.